Analisis Yuridis Normatif Perlindungan Hukum Terhadap Anak Korban Tindak Pidana Pencabulan, Ditinjau Dari Hukum Positif (Studi Kasus Putusan Pengadilan Negeri Lamongan. Nomor: 53/PID.SUS/2018) - Muhammad Yanto; Munif Rochmawanto (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2022)
Children are the next generation of the nation's ideals, therefore the commitment and treatment to pay attention to the development and role of children as the next generation of the nation is something that must be held by the government. Children who are not yet mature mentally and physically, their needs must be fulfilled, their opinions must be respected and given a correct and conducive education, because children in the period of personal and psychological growth and development can grow and develop into children who can be cared for. pkan as the nation's successor. The author wants to take an approach by examining the normative juridical concept of criminal cases of obscenity of minors (pedophilia). Case Study Verdict Number: 53/Pid.Sus/2018/PN.Lmg. The type of research used is a descriptive type of research, to provide a complete picture of a positive legal review in this case Law Number: 35 of 2014 Amendments to Law Number: 23 of 2002 concerning Child Protection and also in the criminal act of obscenity against minors (pedophilia). Children who are victims of obscenity are entitled to treatment, rehabilitation, psychologist assistance, assistance from investigation, prosecution to court, this is stated in Article 69A, and victims who are entitled to apply for restitution rights are regulated in Article 71D.  Special protection for children victims of sexual crimes as referred to in Article 59 Paragraph Letter j is carried out through efforts, namely education about reproductive health, religious values, and moral values; social rehabilitation; psychosocial assistance at the time of treatment to recovery, and; providing protection and assistance at every level of examination ranging from investigation,  prosecution, to examination in court siding and the existence of criminal sanctions that imposed on the perpetrators contained in Article 82 of Law Number 35 of 2014 concerning Child Protection..